On Higher-Order Sensitivity Analysis of Parametric Henig Set-Valued Equilibrium Problems. (18th November 2019) - Anh, Nguyen Le Hoang
Abstract: In the article, we discuss sensitivity analysis of a parametric Henig set-valued equilibrium problem. In detail, relationships between the higher-order contingent derivative of the solution map of this problem and those of objective and constraint maps are established. Finally, applications to parametric set-valued optimization problems are given.